Analysis of Learning Difficulties for Students of MAN 2 Makassar - Vega, Nadya Maharani; Damaiyanti, Annisa Anugrah; Arhamar, A. S. Muhammad; Ami, Agung Wijaya; Saparuddin, Saparuddin (PT ARRUS Intelektual Indonesia, 2023)
One of the causes of the decline in the quality of education is the large number of students who experience learning difficulties. The purpose of this study was to determine the learning difficulties experienced by students in class XI MAN 2 Makassar. The aspects observed in learning difficulties at MAN 2 Makassar include learning motivation, learning media, learning processes, use of learning tools, as well as learning support facilities and facilities. This study uses a quantitative approach using a survey method research type. The population in this study were students from class XI MIPA at MAN 2 Makassar and the sample in this study were students from MAN 2 Makassar class XI MIPA 1 and MIPA 2 with a total of 53 participants. The data collection technique uses a survey which contains 30 questions developed based on aspects of learning difficulties and distributed via the Google form. The results showed that the learning difficulties of students in class XI MIPA at MAN 2 Makassar in the aspect of learning motivation had a moderate categorization with an index of 55.07%, low learning media with an index of 79.4%, a low learning process with an index of 74%, the use of learning tools low with an index of 66.7% and learning support facilities and facilities which are classified as low with an index of 66.1%.